Review of Kernels for Droplet-Droplet Interaction, Droplet-Wall Collision, Entrainment, Re-entrainment, and Breakage - Marchetti, Jorge Mario (2012)
Gas purification is one of the most common and important process steps in combined oil and gas production in order to obtain a product meeting the required export specifications. One of the separation steps is droplet removal, which may be found in several positions in a gas processing train. Gas dehydration, sweetening, and, in particular, compression are very dependent on an almost droplet-free gas. The equipment normally used for this purpose is a so-called scrubber, where the droplets are usually removed in three stages. The process of droplet removal is governed by several physical phenomena, such as droplet-droplet interaction, droplet deposition on dry and wet walls, droplet re-entrainment by the gas flow, coalescence, and breakage. For each of them closure laws are needed, and several kernels have been developed in order to establish in what operational domain and under which specific conditions the various phenomena dominate, can be minimized, or can be eliminated this article is a review of the individual physical processes, and the models developed to describe these including advantages and shortcomings of each of them. © 2012 Copyright Taylor and Francis Group, LLC.